Thermally evaporated CZTSe thin films for solar cell application: Study on the effect of annealing time. (2nd January 2020) - Henry, J.; Mohanraj, K.; Sivakumar, G.
ABSTRACT: In this paper, Cu2 ZnSnSe4 (CZTSe) thin films were prepared by thermal evaporation method and annealed at 300°C for three different annealing time (2, 4, and 6 h) in air atmosphere. The XRD studies indicates that the as deposited films shows amorphous nature and annealed films confirms the formation of CZTSe compound and its average crystallite size increase with increase in annealing time. Among the films, the 2 h annealed film shows higher crystallinity. AFM images show bigger size particels for annealed films. DRS spectra of all the films show good optical absorption in the entire visible range and the band gap is found in the range of 1.45–1. 54 eV. Therefore the annealed films show good photosensing behavior.